Case report: A family of atypical hemolytic uremic syndrome involving a CFH::CFHR1 fusion gene and CFHR3-1-4-2 gene duplication - Tasaki, Yuko; Tsujimoto, Hiroshi; Yokoyama, Tadafumi; Sugimoto, Naotoshi; Kitajima, Shinji; Fujii, Hiroshi; Hidaka, Yoshihiko; Kato, Noritoshi; Maruyama, Shoichi; Inoue, Norimitsu; Wada, Taizo (Frontiers in Immunology, 2024)
Mutations in the complement factor H (CFH) gene are associated with complement dysregulation and the development of atypical hemolytic uremic syndrome (aHUS). Several fusion genes that result from genomic structural variation in the CFH and complement factor H-related (CFHR) gene regions have been identified in aHUS. However, one allele has both CFHR gene duplication and CFH::CFHR1 fusion gene have not been reported.An 8-month-old girl (proband) presented with aHUS and was treated with ravulizumab. Her paternal grandfather developed aHUS previously and her paternal great grandmother presented with anti-neutrophil cytoplasmic antibody-associated vasculitis and thrombotic microangiopathy (TMA). However, the proband's parents have no history of TMA. A genetic analysis revealed the presence of CFH::CFHR1 fusion gene and a CFHR3-1-4-2 gene duplication in the patient, her father, and her paternal grandfather.Although several fusion genes resulting from structural variations of the CFH-CFHR genes region have been identified, this is the first report of the combination of a CFH::CFHR1 fusion gene with CFHR gene duplication. Because the CFH-CFHR region is highly homologous, we hypothesized that CFHR gene duplication occurred. These findings indicate a novel pathogenic genomic structural variation associated with the development of aHUS.